Identification of a new coronavirus-specific RNA export protein complex - Bárcena-Martin, Montse (Henry Stewart Talks, 2020)
Rationale for the search and investigation of coronavirus-specific replication machinery, Identification of a new coronavirus-specific RNA export protein complex, The stages of coronavirus entry into human cells and the role of the RNA export complex, Innovative research approaches to the detection of the new protein complex, Implications for the development of coronavirus-specific antiviral drugs, Next steps in the characterization of the new protein complex as a drug target